Incorporation of the Lean Construction model to innovate time management in construction projects - Murillo Manrique, Margarita (2024)
In the construction industry, productivity is sought to improve by innovating time management, a poor indicator in projects where activities are executed conventionally. In this sense, the research aims to evaluate the consequences of delays in projects and how to optimize time by incorporating the Lean Construction model. The procedure considers the review of bibliographic material, articles, construction magazines and projects that propose innovating time management with the Lean Construction model through the tools Last Planner System (LPS), productivity balance sheet, productive work (TP). , contributory work (TC), non-contributory work (TNC), percentage of parts completed (PPC) and application of the 5”s” tool. The results found that support the article correspond to the Barranco 360° project located in Lima that includes information on the productivity balance chart close to 80%, TP (40%), TC (41%) and TNC (19%), to the project Residencial Gold San Francisco in Cusco with a productivity index of 39.5% and project “A” with a productivity deficiency of 20% in its construction works. It is concluded that the statistical results applying Lean Construction tools allow time management, mitigating restrictions and providing quick and efficient solutions, optimizing productivity without neglecting quality in the execution of the project.